La Delincuencia y su Incidencia en la Inversión Extranjera Directa en el Ecuador, Periodo 2001-2021. - Vicuña Matute, Jhoselin Briggite (2022)
This research analyzes the incidence of crime in FDI in Ecuador during the period 2001 - 2021, the purpose of this research is to determine how crime influences FDI. Three variables related to investment were obtained: country risk, GDP and the homicide rate to determine the impact of criminal acts. This document is made up of four chapters. Chapter I, Shows the presentation of the topic to introduce the reader to the subject and outlines the problem and justification. Chapter II covers the theoretical part which details: concepts, classifications, theories concerned, and evidence; which showed a negative relationship between the main variables. Chapter III covers the methodological issue, where the ARDL model used, the data, sample and type of research are described, the econometric calculations showed the same long-term relationship under the Bounds test, which is used in small samples in contrast to Johansen's. Finally, the recommendations were strengthened and in accordance with the determinations, it was concluded that the homicide rate decreased FDI by 1.31%, for which it was suggested to place greater emphasis on citizen security.